Risk management related to long-term mine gas emissions: feedback from a French experience - Lafortune, S.; Herbout, A.; Lefebvre, O.; Arnone, T.; Tardivon, J.; Bigarré, P. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Mine closure activities in underground mines lead to stopping water pumping and ventilation systems. Unflooded voids form reservoirs where dangerous air or toxic gas can appear. Adits, shafts or boreholes shape potential migration pathways for gas transfer to the surface but also fresh air entrances. Gas can also migrate through overburden if it is fractured by former underground mining activities. Eventually gas migration between mining voids and the surface is mostly driven by temperature and pressure gradients that cyclically change with seasons. Gases constituting the atmospheres within underground old mines have several possible origins: surface ‘fresh’ air entrance, degassing from rock formations (e.g. coal seams), deep gas seepage (e.g. mantle gas), redox or acid-base reactions, biological processes, etc. Any underground mining context may be affected by risks related to mine gas. Usual components of mine gas are nitrogen, oxygen, carbon dioxide, methane, carbon monoxide and hydrogen sulphide. Once emitted to the surface, mine gas may lead to hazardous situations for people. Related hazards are explosion, suffocation and poisoning. Underground mine gas reserves, migration pathways, the composition of the emitted gas, the dynamics of the emission (flow, duration) and the potential of accumulation in dwellings, confined or semi-confined premises (i.e. poorly ventilated spaces such as cellars, basements, underground networks and inspection hatches) must be considered when managing the risks. In two case studies of populated areas we illustrate how risks related to mine gas emissions to the surface are managed in France: the first in a former coal basin and the second in a former iron ore mining area. Authors detail how mine gas monitoring helps to understand underground gas production processes and gas migration transfers to the surface. They also describe mitigation measures implemented and provide feedback based on French experiences.